El Partido Comunista de Argentina y los orígenes del peronismo. Un análisis desde su estrategia de Frente Popular - Gabriel Piro Mittelman (Nuevo mundo - Mundos Nuevos, 2021)
The objective of this work is to analyze the political performance of the Communist Party of Argentina (CP) in the particular conjuncture of 1945, at which time, on the one hand, the crisis of the regime inaugurated in June 1943 deepens, and on the other, the formation of Peronism. From the analysis of various sources, we will observe the way in which the Popular Front strategy, which articulated the development of the CP since 1935, delimited the contours of its experience at this stage.